Developing self-efficacy through a massive open online course on study skills - Padilla Rodríguez, Brenda Cecilia; Armellini, Alejandro (International Council for Distance Education, 2017)
Self-efficacy is a strong predictor of academic performance, and an area of interest for higher education institutions. This paper reports on a massive open online course (MOOC) on study skills, aimed at increasing self-efficacy. Participants (n=32) were from Mexico and Colombia, with ages ranging from 21 to 45 years. At the beginning and the end of the MOOC, learners answered a survey that included the General Self-Efficacy Scale, items on specific study skills, and space for optional comments. Findings show statistically significant increases in general self-efficacy after completing the MOOC, as well as in the perceived self-efficacy related to five out of six study skills. Comments suggest that participants are aware of and value their own improvement. For students, MOOCs can represent low-risk, formative opportunities to widen their knowledge and increase their self-efficacy. For academic institutions, well-designed MOOCs on study skills provide a means to support students.